The effect of Global Postural Reeducation on body weight distribution in sitting posture and on musculoskeletal pain. A pilot study - Lima e Sa Resende, Fernanda de; Vanti, Carla; Banchelli, Federico; Trani Brandao, Jose Geraldo [UNESP]; Oliveira Amorim, Jose Benedito [UNESP]; Villafae, Jorge Hugo; Guccione, Andrew; Pillastrini, Paolo (Mattioli 1885, 2017)
Objective: To quantify body weight distribution (BWD) in seated posture with an office chair instrumented with load cells and to evaluate the effects of ergonomic advice and Global Postural Reeducation (GPR) on seated BWD and on musculoskeletal pain. Methods: Nineteen healthy females were randomly assigned: nine to the experimental group and 10 to the control group. Control group (CG) received only ergonomic verbal advice (EVA) regarding BWD in a seated position. Experimental group (EG) also received EVA and furthermore attended eight GPR sessions. Difference in the effects of the different therapeutic approaches was investigated using the non-parametric Wilcoxon-Mann-Whitney test. Results: After treatments, there was no significant difference between the two groups as regards seated BWD. EG improved musculoskeletal pain significantly more than CG (p<0.005). Instead, musculoskeletal pain frequency decreased (p<0.005) only in EG (after EVA and GPR sessions), in neck, cervical, thoracic, lumbar, shoulders and wrists areas. Conclusions: Despite both interventions did not induce any significant improvement on seated BWD, adding GPR to EVA was related to a better reduction on musculoskeletal pain in young health females.
Keywords: Global postural reeducation; body weight distribution; posture; pain; ergonomics